(untitled) (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Human Resources (HR) in schools, especially educators, are teachers. There are at least three types of teacher duties in carrying out their duties, namely preparing learning (planning), implementing learning (actuating), and evaluating learning (evaluation) both in terms of cognitive, affective and psychomotor aspects. However, in its implementation, many teachers experience problems or issues that are faced. For that, as a Supervisor at school, of course, you can help teachers who face various problems or issues in their duties as educators. Therefore, this discussion focuses on teachers to help overcome their problems, namely Several Problems Faced by Teachers in Their Duties at School. With the hope that teacher problems can be resolved and at the same time can improve the quality of the learning process at school